A continuous heat treatment process and system for prestressed anchors
Patent Information
- Application Number
- CN202610917832.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-09-29
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种预应力锚具连续式热处理工艺与系统,解决了现有预应力锚具在淬火时锥形内孔会残留蒸汽膜导致内外壁冷却不均及引发微裂纹,以及水基淬火介质在连续作业中会发生温度分层和聚合物聚集而影响工艺稳定性的问题
本发明通过采用双回路流体调度配合底部射流喷嘴阵列,主循环回路维持宏观水温基础冷速,侧线回路对上层提取流体进行补温和高剪切分散,处理后的侧线流体垂直冲击锚具锥形内孔,破坏孔内积聚的蒸汽膜层,促使聚合物在内孔壁附着成膜,这种物理调控方式改变锚具内孔的换热边界条件,缩小锚具内外壁的冷却速度差,有助于减少马氏体转变不均匀和热应力引发的微裂纹。
Smart Images

Figure CN122833240A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal heat treatment technology, specifically to a continuous heat treatment process and system for prestressed anchors. Background Technology
[0002] Prestressed anchorages are load-bearing anchorages in prestressed concrete structures. Their service conditions require materials with high strength and good toughness. To meet these mechanical properties, the anchorages need to undergo heat treatment processes such as quenching and tempering. Currently, the industry mostly uses continuous mesh belt furnaces combined with water-based quenching media to perform heat treatment on the anchorages.
[0003] Prestressed anchors have a conical inner hole structure. When they fall into the quenching tank and come into contact with the quenching fluid, the inner hole area is limited by space and has a change in cross-sectional dimensions. After the fluid enters the hole and is heated and vaporized, a stable vapor film will form on the surface of the hole wall. This vapor film hinders the direct heat exchange between the liquid fluid and the high-temperature metal surface, and is difficult to discharge smoothly due to the geometry of the hole. This phenomenon causes the cooling rate of the inner hole area of the anchor to be lower than that of the outer surface, resulting in differences in the phase transformation time and volume fraction of the inner and outer walls and the core during the martensitic transformation process. The resulting superposition of structural stress and thermal stress will cause the local hardness of the anchor to be substandard, or microcracks to be induced at the stress concentration points in the hole.
[0004] Furthermore, in continuous mass production processes, the fluid in the quenching tank is in a state of absorbing heat from the workpiece for a long time. After long-term alternation of hot and cold, conventional water-based polymer quenching media will cause temperature gradient stratification in the fluid in the tank. The fluid in the upper layer with higher temperature will cause local aggregation of polymer molecules, affecting the dispersion stability of the medium. As the operation time is extended, polymer agglomeration or precipitation will occur in the quenching liquid, thereby changing the original cooling characteristics of the fluid. This continuous fluctuation in the state of the medium increases the difficulty of controlling the continuous heat treatment process and has an adverse effect on the stability of product quality between batches. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a continuous heat treatment process and system for prestressed anchors, which solves the problems of residual vapor film in the conical inner hole during quenching of existing prestressed anchors, leading to uneven cooling of the inner and outer walls and causing microcracks, as well as the problems of temperature stratification and polymer aggregation in water-based quenching media during continuous operation, affecting process stability.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a continuous heat treatment process for prestressed anchorages, the process comprising the following steps: Prepare water-based quenching medium and inject it into the quenching tank and pipeline; The prestressed anchorage is placed in a heating furnace for heat preservation to achieve complete austenitization; During the process of the prestressed anchor falling into the quenching tank, a dual-loop fluid scheduling is performed: the main circulation pump draws the fluid from the lower part of the quenching tank, and the water temperature in the quenching tank is kept constant through the main circulation cooling heat exchanger; the liquid level overflow pump extracts the upper part of the fluid below the liquid level in the quenching tank as the side-line fluid, and the side-line fluid is heated by the heat exchanger and then fed into the high-shear homogenizing pump to apply shear force through the stator-rotor gap for mechanical crushing and dispersion. After being mechanically crushed and dispersed, the side-stream fluid is sprayed vertically upward through the bottom jet nozzle array to impact the conical inner hole of the prestressed anchor falling into the quenching tank for staged cooling. After the prestressed anchorage cools down, it is removed from the quenching tank and sent to the tempering furnace for heat preservation. After being removed from the furnace and air-cooled, the heat-treated prestressed anchorage is obtained.
[0007] By adopting the above technical solution, this process uses a combination of dual-loop fluid scheduling and bottom vertical jetting to address the physical phenomenon of gradient distribution of fluid temperature and concentration in the quenching tank. The main circulation loop maintains the basic cooling rate of the macroscopic large-volume fluid in the tank, while the side loop specifically extracts the top layer fluid containing high heat and where polymer flocculation occurs. The extracted top layer fluid is heated to above the inverse melting point temperature of polyalkylene glycol using a heat exchanger, which promotes the desolvation and precipitation of polymer from the aqueous phase.
[0008] With the high-speed mechanical shearing action of the high-shear homogenizing pump, the large polymer droplets that have been desolventized are pulverized into micron-sized uniform emulsions. The treated side-stream emulsion directly impacts the conical inner hole of the falling anchor in the form of a vertically upward high-kinetic-energy jet. With the mechanical scouring force of the jet, the initial vapor film layer inside the hole is instantly destroyed. After the homogenized and desolventized polymer microdroplets in the fluid come into contact with the high-temperature metal surface, they quickly attach and cross-link to form a liquid polymer coating with a relatively uniform thickness.
[0009] The liquid polymer coating acts as a thermally conductive and thermally resistive layer, causing the surface heat flux density of the anchor to decrease when it passes through the coating uniform temperature zone. This leads to a rapid convergence of the temperature difference between the inner and outer walls, thus guiding the austenite to martensite transformation process to proceed smoothly. As the anchor sinks into the convection cooling zone, the flow rate decreases, and the polymer coating re-dissolves in the water as the temperature drops. The metal surface then returns to pure liquid convection heat transfer to complete the cooling process. This mechanism effectively improves the problem of the vapor blind zone in the anchor's inner hole and, to a certain extent, suppresses the risk of cracking caused by thermal stress and structural stress.
[0010] Preferably, the water-based quenching medium is made from the following raw materials in parts by weight: deionized water: 86.8 to 91.4 parts; polyalkylene glycol: 8.0 to 12.0 parts; sodium metasilicate: 0.4 to 0.8 parts; sodium polyaspartate: 0.2 to 0.4 parts.
[0011] By adopting the above technical solutions, the basic content of polyalkylene glycol is controlled to provide the function of reverse solubility film formation in quenching media; sodium metasilicate establishes an alkaline buffer environment in the system and forms a silicate protective film with anti-rust effect on the surface of anchors; sodium polyaspartate, as a scale inhibitor and dispersant, utilizes the electrostatic repulsion effect generated by the carboxyl anions on the sodium polyaspartate molecular chain to maintain the dispersion stability of polyalkylene glycol and sodium metasilicate in the aqueous system, and reduces the possibility of agglomeration and precipitation of the media during continuous alternating hot and cold operations.
[0012] Preferably, the polyalkylene glycol is made from the following raw materials in parts by weight: n-butanol: 0.55 to 0.60 parts; potassium hydroxide: 0.1 to 0.3 parts; ethylene oxide: 45.0 to 55.0 parts; propylene oxide: 45.0 to 66.0 parts.
[0013] By adopting the above technical solution, n-butanol is used as an initiator and potassium hydroxide as a catalyst in the synthesis of polyalkylene glycol. Regarding the chemical reaction mechanism, the hydroxyl groups of n-butanol form oxygen anions under alkaline conditions, which initiate the ring-opening polymerization of ethylene oxide and propylene oxide monomers. The ethylene oxide segments provide hydrophilicity, and the propylene oxide segments provide hydrophobicity. By setting the weight ratio of ethylene oxide to propylene oxide, the spatial arrangement of hydrophilic and hydrophobic groups in the copolymer molecular chain is controlled. This ratio setting makes the synthesized polyalkylene glycol have a suitable cloud point, which is conducive to the phase separation and precipitation of polyalkylene glycol when it comes into contact with the heated anchor, thus constructing a polymer coating that meets the cooling rate requirements of the prestressed anchor.
[0014] Preferably, the polyaspartic acid sodium salt is made from the following raw materials in parts by weight: L-aspartic acid: 100.0 to 110.0 parts; deionized water: 180.0 to 220.0 parts; and sodium hydroxide aqueous solution with a mass fraction of 20% to 30%: 110.0 to 150.0 parts.
[0015] By adopting the above technical solution, the synthesis mechanism of sodium polyaspartate includes a condensation stage and an alkaline hydrolysis ring-opening stage. In the condensation stage, L-aspartic acid undergoes intermolecular dehydration condensation under heating and vacuum conditions to generate a solid polysuccinimide with a five-membered ring structure. After adding an aqueous sodium hydroxide solution, it enters the alkaline hydrolysis ring-opening stage, where the imide ring on the polysuccinimide main chain undergoes a nucleophilic ring-opening reaction, transforming into sodium polyaspartate segments with free carboxylate groups. The limited ratio of reactants promotes the ring-opening reaction, resulting in a larger number of carboxylate groups on the polymer side chains. This enhances the steric hindrance effect and the ability to complex calcium and magnesium ions in the quenching medium system, reducing the risk of scaling in the quenching medium at high temperatures.
[0016] Preferably, in the step of placing the prestressed anchor in a heating furnace for heat preservation to achieve complete austenitization, the operating temperature of the heating furnace is 840°C to 860°C, and the carbon potential is 0.40%C to 0.45%C. In the step of removing the prestressed anchor from the quenching tank after it has cooled down and sending it to the tempering furnace for heat preservation, the temperature of the prestressed anchor is 80℃ to 120℃ when it is removed from the quenching tank; the working temperature of the tempering furnace is 180℃ to 220℃, and the heat preservation time is 90 to 120 minutes.
[0017] By adopting the above technical solution, the working temperature of 840 to 860℃ is conducive to the dissolution of carbides and the uniform nucleation of austenite grains in prestressed anchors made of 40Cr material. The carbon potential of 0.40% to 0.45% matches the carbon content of the base material, which can avoid surface decarburization or overcarburization from affecting the surface hardness to a certain extent. By controlling the exit temperature at 80 to 120℃, the residual heat inside the anchor is used to evaporate the moisture on the surface of the anchor, reducing the need for additional cleaning and drying processes. Since the anchor has completed the martensitic transformation at this time, the subsequent low-temperature tempering operation at 180 to 220℃ helps to eliminate quenching residual stress, stabilize the microstructure and size, and thus improve the strength and toughness of the anchor.
[0018] Preferably, in the step of the main circulation pump drawing fluid from the lower part of the quenching tank and maintaining the water temperature in the quenching tank at a constant temperature through the main circulation cooling heat exchanger, the water temperature is kept constant at 40°C to 45°C. The overflow pump extracts the upper fluid below the liquid surface in the quenching tank as a side-stream fluid. After being heated by a heat exchanger, the side-stream fluid is fed into a high-shear homogenizing pump for mechanical pulverization and dispersion using shear force applied by the stator-rotor gap. The side-stream fluid is extracted from a depth of 0 to 200 mm below the liquid surface directly above the prestressed anchor's water-falling area, accounting for 15% to 20% of the total flow rate. The heated side-stream fluid reaches a temperature of 65°C to 70°C. The high-shear homogenizing pump applies a shear rate of 5000 s⁻¹. -1 up to 8000s -1 .
[0019] By employing the above technical solution, an extraction zone with a depth of 0 to 200 mm below the liquid surface is set, avoiding floating impurities on the surface of the tank and the deep low-temperature reflux zone. The upper heat-affected fluid, with a higher concentration and temperature, is collected. This portion of the fluid, accounting for 15% to 20%, is then separately heated to 65 to 70°C, exceeding the cloud point of polyalkylene glycol. This causes liquid-liquid phase separation of the polymer before it enters the jet nozzle, with a binding time of 5000 to 8000 seconds. -1 The shear rate cuts the free polymer agglomerates into suspended micro-droplets. The above physical control means that the ejected fluid has better spreading and adhesion ability, shortens the lag time of conventional quenching fluid contacting high-temperature workpieces, which requires absorbing heat before polymer precipitation, and improves the film formation efficiency for conical inner holes.
[0020] Preferably, the step of performing staged cooling and temperature reduction specifically involves the following steps: the prestressed anchor sequentially undergoes a transient film-breaking zone, a coating homogenization zone, and a convection cooling zone within the quenching tank. The transient film-breaking zone lasts for 2 to 4 seconds, with the side-stream fluid being vertically injected upwards at a local flow velocity of 1.8 m / s to 2.5 m / s. The coating homogenization zone lasts for 10 to 14 seconds, with a local flow velocity of 0.1 m / s to 0.3 m / s in a laminar flow state. The convection cooling zone continues until the prestressed anchor is removed from the quenching tank, with a local flow velocity of 0.5 m / s to 0.8 m / s.
[0021] By adopting the above technical solution, the cooling process of the anchor is spatially divided by the kinetic energy of the flow field. In the transient film-breaking zone of 2 to 4 seconds, a kinetic energy jet of 1.8 to 2.5 m / s is used to disperse the vapor film generated in the inner hole when the anchor enters the water, guiding the polymer film to attach. After entering the coating uniform temperature zone, the flow velocity drops to a laminar flow state of 0.1 to 0.3 m / s and continues for 10 to 14 seconds, thereby protecting the formed liquid polymer coating from being destroyed by the water flow. The cooling rate is limited by the thermal resistance characteristics of the coating, guiding the temperature field of the inner and outer walls to become more uniform, so as to complete the martensitic phase transformation in the core. The flow velocity in the convection cooling zone rises back to 0.5 to 0.8 m / s, accelerating heat dissipation and adapting to the cycle requirements of the workpiece cooling after leaving the tank.
[0022] Preferably, the polyalkylene glycol has a weight-average molecular weight of 12,050 to 14,960 and a cloud point of 60°C to 65°C for a 10% aqueous solution; the sodium polyaspartate has a weight-average molecular weight of 3,120 to 4,950.
[0023] By adopting the above technical solution, polyalkylene glycol with a weight-average molecular weight of 12050 to 14960 is used to ensure that the polymer film formed after the polyalkylene glycol precipitation has a suitable viscosity and thickness to play a role in heat insulation. Too high a molecular weight will lead to increased workpiece drag loss, while too low a molecular weight will result in weak film formation. The cloud point is controlled at 60 to 65°C, and the side-stream fluid heating parameters are matched to form the effective point of thermal phase separation. The molecular weight of sodium polyaspartate is limited to 3120 to 4950, which makes it difficult for the polymer chain segment length to generate self-flocculation. At the same time, it can provide negative charge sites with a certain distribution density for dispersion and stability in water systems.
[0024] Preferably, the bottom jet nozzle array is located at the bottom of the quenching tank, which is used to make the side jet fluid spray vertically upward and impact the conical inner hole of the prestressed anchor falling into the quenching tank.
[0025] By adopting the above technical solution, the vertically upward jet direction and the steam discharge direction rising due to buoyancy produce a superposition effect in the same direction. The kinetic fluid enters the conical inner hole of the prestressed anchor from bottom to top. According to the cross-sectional contraction geometry of the conical hole, the fluid generates a squeezing effect in the hole. This fluid form helps to peel off the residual vaporized film layer in the hole, and promotes the inner hole wall and the outer surface to be consistent in terms of heat transfer boundary conditions.
[0026] Secondly, the present invention also provides a system for a continuous heat treatment process for prestressed anchorages, the system comprising: A heating furnace is used to place and insulate prestressed anchorages to achieve complete austenitization. Quenching tank, used to contain water-based quenching medium and receive prestressed anchors dropped into it; The main circulation pump and the main circulation cooling heat exchanger are connected to the lower part of the quenching tank to extract fluid from the lower part of the quenching tank. The main circulation cooling heat exchanger is connected to the main circulation pump and is used to cool the extracted fluid and circulate it back to the quenching tank to maintain a constant water temperature in the quenching tank. The system consists of a liquid level overflow pump, a heat exchanger, and a high-shear homogenizing pump connected in series. The liquid level overflow pump is used to extract the upper fluid below the liquid level in the quenching tank as a side-stream fluid. The heat exchanger is used to heat the side-stream fluid. The high-shear homogenizing pump is used to apply shear force to the heated side-stream fluid using the stator-rotor gap for mechanical crushing and dispersion. The bottom jet nozzle array is connected to the outlet of the high-shear homogenizing pump and located at the bottom of the quenching tank. It is used to vertically spray the side-stream fluid after mechanical crushing and dispersion upwards to impact the conical inner hole of the prestressed anchor that falls into the quenching tank. A tempering furnace is used to receive prestressed anchors that have been removed from the quenching tank.
[0027] By adopting the above technical solution, the heating furnace and the continuous quenching tank are adapted to the feed and discharge cycle of the assembly line. The system constructs two independent fluid control loops. The basic loop, consisting of the main circulation pump and the heat exchanger, maintains the fluid in the entire tank at the basic working water temperature. The side loop, consisting of the liquid surface overflow pump, the heat exchanger, and the high shear homogenizing pump connected in series, physically regulates the imbalance of spatially distributed heat and molecular polymerization state.
[0028] The heat exchanger provides the thermal energy conditions to induce phase separation, and the high-shear homogenizing pump uses mechanical work to refine and distribute the phase-separated droplets. The jet nozzle array arranged at the bottom of the tank transports the treated homogenous emulsion to the space area where the water-drop anchor is located. The above system architecture separates the two tasks of macroscopic cooling and microscopic media state intervention, making it difficult for fluid performance to decline when the number of processed parts increases during the continuous quenching process. From the equipment structure level, it reduces the probability of cold quenching cracking of the inner hole of the prestressed anchor and the occurrence of heat treatment quality fluctuations.
[0029] This invention provides a continuous heat treatment process and system for prestressed anchors, which has the following beneficial effects: This invention employs a dual-loop fluid regulation system in conjunction with a bottom jet nozzle array. The main circulation loop maintains the macroscopic water temperature and basic cooling rate, while the side-loop replenishes the temperature and disperses the extracted fluid from the upper layer at high shear rates. The treated side-loop fluid vertically impacts the conical inner hole of the anchor, breaking down the vapor film layer accumulated inside the hole and promoting polymer adhesion and film formation on the inner hole wall. This physical regulation method alters the heat transfer boundary conditions of the anchor's inner hole, reduces the cooling rate difference between the inner and outer walls of the anchor, and helps to reduce uneven martensitic transformation and microcracks caused by thermal stress.
[0030] This invention spatially divides the cooling process of prestressed anchors by setting a three-stage flow rate control model consisting of a transient film-breaking zone, a coating homogenization zone, and a convection cooling zone. In the initial stage of water immersion, a high-velocity jet is used to disperse the vapor film; then the flow rate is reduced to enter a laminar flow state, protecting the formed liquid polymer coating to limit the surface heat flux density and guiding the internal and external temperature fields of the workpiece to approach the completion of the phase transformation; finally, the flow rate is increased again for conventional convection cooling. This stepped flow rate design matches the cooling phase transformation requirements of the workpiece after austenitization, improving the stability of the workpiece's continuous heat treatment quality.
[0031] The water-based quenching medium of this invention contains polyalkylene glycol with a specific molecular weight and cloud point, and is compounded with sodium polyaspartate and sodium metasilicate. The ratio of ethylene oxide to propylene oxide is controlled during the synthesis of polyalkylene glycol, so that the polymer can undergo liquid-liquid phase separation after heat exchange. Sodium polyaspartate provides steric hindrance and electrostatic repulsion. The combination of the above material components maintains the dispersion state of the polymer in the aqueous system, reduces the probability of agglomeration, precipitation and scaling of the quenching medium in long-term continuous hot and cold cycle operation, and extends the service life of the quenching fluid. Attached Figure Description
[0032] Figure 1 This is a test diagram of the particle size distribution of the dispersed phase in the side-line fluid of the present invention; Figure 2 This is a partial infrared spectrum of the polymer dry film of the present invention; Figure 3 This is a thermogravimetric analysis curve of the polymer dry film of the present invention; Figure 4 This is a bubble distribution diagram illustrating the cooling state evolution under the simulated flow field within the internal bore of the present invention. Figure 5 Figure 1 shows the contour map of the hardness distribution of the inner hole wall of the prestressed anchor in the longitudinal section of the present invention. Figure 2 shows the contour map of the hardness distribution of the test sample of the prestressed anchor in Example 1, and Figure 3 shows the contour map of the hardness distribution of the test sample of the prestressed anchor in Comparative Example 1. Figure 6 A schematic diagram of the system architecture of this invention. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0035] Ethylene oxide, CAS number 75-21-8, liquid form with a purity greater than 99.9 wt%; Propylene oxide, CAS number 75-56-9, purity greater than 99.9 wt%; L-Aspartic acid, CAS number 56-84-8, purity greater than 99.0 wt%; Sodium metasilicate, CAS No. 6834-92-0, modulus 2.2 to 2.5, sodium oxide mass fraction 28 wt% to 30 wt%, silicon dioxide mass fraction 66 wt% to 68 wt%.
[0036] In this invention, the units of measurement for all materials and solvents are uniformly referred to as parts by weight.
[0037] Preparation Example 1: This preparation example provides a method for preparing polyalkylene glycol, including the following steps: 0.55 parts n-butanol and 0.1 parts potassium hydroxide were added to a reaction vessel. Stirring was started and nitrogen gas was introduced to replace the air in the vessel. The temperature was raised to 110°C. Then, a mixed monomer consisting of 45.0 parts ethylene oxide and 45.0 parts propylene oxide was continuously added dropwise to the reaction vessel. The pressure in the reaction vessel was controlled at 0.2 MPa to carry out the random copolymerization reaction. After the mixed monomer was added, the temperature was maintained for aging reaction for 1.5 hours. After the reaction was completed, the temperature was lowered to 75°C, and glacial acetic acid was added to neutralize to a pH of 7.0. After vacuum dehydration, polyalkylene glycol with a weight average molecular weight of 12050 and a mass fraction of 10% and a cloud point of 65°C was obtained for use. The polyalkylene glycol here is named polyalkylene glycol A.
[0038] Preparation Example 2: This preparation example provides a method for preparing polyalkylene glycol, including the following steps: 0.58 parts of n-butanol and 0.2 parts of potassium hydroxide were added to a reactor. Stirring was started and nitrogen gas was introduced to replace the air in the reactor. The temperature was raised to 120°C. Then, a mixed monomer consisting of 50.0 parts of ethylene oxide and 55.0 parts of propylene oxide was continuously added dropwise to the reactor. The pressure in the reactor was controlled at 0.3 MPa to carry out the random copolymerization reaction. After the mixed monomer was completely added, the reaction was kept at the temperature for aging for 2.0 h. After the reaction was completed, the temperature was lowered to 80°C, and glacial acetic acid was added to neutralize to a pH of 7.0. After vacuum dehydration, polyalkylene glycol with a weight average molecular weight of 13480 and a mass fraction of 10% and a cloud point of 62°C was obtained for use. The polyalkylene glycol here is named polyalkylene glycol B.
[0039] Preparation Example 3: This preparation example provides a method for preparing polyalkylene glycol, including the following steps: 0.60 parts of n-butanol and 0.3 parts of potassium hydroxide were added to a reactor. Stirring was started and nitrogen gas was introduced to replace the air in the reactor. The temperature was raised to 130°C. Then, a mixed monomer consisting of 55.0 parts of ethylene oxide and 66.0 parts of propylene oxide was continuously added dropwise to the reactor. The pressure in the reactor was controlled at 0.4 MPa to carry out the random copolymerization reaction. After the mixed monomer was added, the reaction was kept at the temperature for aging for 2.5 hours. After the reaction was completed, the temperature was lowered to 85°C, and glacial acetic acid was added to neutralize to a pH of 7.0. After vacuum dehydration, polyalkylene glycol with a weight-average molecular weight of 14960 and a mass fraction of 10% and a cloud point of 60°C was obtained for use. The polyalkylene glycol here is named polyalkylene glycol C.
[0040] Preparation Example 4: This preparation example provides a method for preparing sodium polyaspartate, including the following steps: 100.0 parts of L-aspartic acid were placed in a reactor and polycondensed at 220℃ and -0.07MPa for 1.5h. After the reaction, the mixture was cooled to room temperature and mechanically pulverized to generate an intermediate solid polysuccinimide. The obtained solid polysuccinimide was then suspended in 180.0 parts of deionized water and heated to 60℃ with mechanical stirring. 150.0 parts of a 20% sodium hydroxide aqueous solution were slowly added dropwise to carry out an alkaline ring-opening hydrolysis reaction. The pH of the reaction mixture was controlled at 9.0 during the hydrolysis reaction. After the addition was completed, the reaction was kept at the same temperature for 1.5h. After the reaction, the mixture was dehydrated and dried to obtain sodium polyaspartate with a weight average molecular weight of 3120 for later use. The sodium polyaspartate here is named sodium polyaspartate A.
[0041] Preparation Example 5: This preparation example provides a method for preparing sodium polyaspartate, including the following steps: 105.0 parts of L-aspartic acid were placed in a reactor and polycondensed at 230℃ and -0.08MPa for 2.0 h. After the reaction, the mixture was cooled to room temperature and mechanically pulverized to generate an intermediate solid polysuccinimide. The obtained solid polysuccinimide was then suspended in 200.0 parts of deionized water and heated to 70℃ with mechanical stirring. 126.0 parts of a 25% sodium hydroxide aqueous solution were slowly added dropwise to carry out an alkaline ring-opening hydrolysis reaction. The pH of the reaction mixture was controlled at 9.8 during the hydrolysis reaction. After the addition was completed, the reaction was kept at the same temperature for 2.0 h. After the reaction, the mixture was dehydrated and dried to obtain sodium polyaspartate with a weight average molecular weight of 4080 for later use. The sodium polyaspartate here is named sodium polyaspartate B.
[0042] Preparation Example 6: This preparation example provides a method for preparing sodium polyaspartate, including the following steps: 110.0 parts of L-aspartic acid were placed in a reactor and polycondensed at 240℃ and -0.09MPa for 2.5 h. After the reaction, the mixture was cooled to room temperature and mechanically pulverized to generate an intermediate solid polysuccinimide. The obtained solid polysuccinimide was then suspended in 220.0 parts of deionized water and heated to 80℃ with mechanical stirring. 110.0 parts of a 30% sodium hydroxide aqueous solution were slowly added dropwise to carry out an alkaline ring-opening hydrolysis reaction. The pH of the reaction mixture was controlled at 10.5 during the hydrolysis reaction. After the addition was completed, the reaction was kept at the same temperature for 2.5 h. After the reaction, the mixture was dehydrated and dried to obtain sodium polyaspartate with a weight average molecular weight of 4950 for later use. The sodium polyaspartate here is named sodium polyaspartate C.
[0043] Example 1: This embodiment provides a continuous heat treatment process for prestressed anchorages, including the following steps: Weigh 8.0 parts of polyalkylene glycol A, 0.4 parts of sodium metasilicate, 0.2 parts of sodium polyaspartate A and 91.4 parts of deionized water, mix and stir the above components evenly at room temperature, and prepare a water-based quenching medium for injection into the continuous quenching tank and pipeline system.
[0044] Prestressed anchors made of 40Cr material are placed in a mesh belt protective atmosphere heating furnace, which is filled with a protective gas to prevent metal oxidation and decarburization. The furnace operating temperature is set to 840℃ and the carbon potential is controlled at 0.40%C. The prestressed anchors are laid flat on a continuously moving transmission mesh belt inside the furnace. The movement of the mesh belt slowly transports the prestressed anchors from the furnace inlet to the discharge outlet. During the transport process, the prestressed anchors gradually heat up and are continuously kept at that temperature, ultimately achieving complete austenitization.
[0045] During the continuous descent of the prestressed anchors into the quenching tank, the system simultaneously executes dual-loop fluid scheduling. The main circulation pump draws fluid from the lower part of the quenching tank, passing it through the main circulation cooling heat exchanger to maintain a constant macroscopic fluid temperature of 40℃ throughout the quenching tank. Simultaneously, a liquid surface overflow pump extracts 15% of the total flow rate of side-stream fluid from a layer 0 to 100 mm above the prestressed anchor descent area within the quenching tank. This side-stream fluid is fed into a compensating heat exchanger for heating, raising its outlet temperature to 65℃. Subsequently, the side-stream fluid enters a high-shear homogenizing pump, where the narrow gap between the high-speed rotating rotor and the stationary stator applies pressure to the fluid for 5000 seconds. -1 Mechanical pulverization and dispersion are performed using a shear rate.
[0046] After the prestressed anchor falls into the quenching tank, it undergoes phased cooling along the conveying trajectory within the tank. Specifically, it passes through three spatial flow field zones in sequence: First, it enters the transient film-breaking zone from 0 to 2 seconds after falling into the water. In this zone, the 65°C side-stream fluid, after mechanical crushing and dispersion, is vertically sprayed upwards through the bottom jet nozzle array at a local velocity of 1.8 m / s, impacting the conical inner hole of the prestressed anchor. Next, it enters the film-coating and temperature-equalizing zone from 2 to 12 seconds after falling into the water. In this zone, the local velocity is controlled at a laminar flow state of 0.1 m / s, and the macroscopic temperature of the fluid in contact with the surface of the prestressed anchor recovers to 40°C. Finally, it enters the convective cooling zone from 12 seconds after falling into the water until exiting the tank. In this zone, the local velocity is controlled at 0.5 m / s, and the temperature is maintained at 40°C.
[0047] When the overall temperature of the prestressed anchor drops to 80℃, it is removed from the quenching tank. After the surface moisture is evaporated by the residual heat of the prestressed anchor, it is sent to a continuous tempering furnace and held at 180℃ for 90 minutes. After being removed from the furnace and air-cooled, the heat-treated prestressed anchor is obtained.
[0048] Example 2: This embodiment provides a continuous heat treatment process for prestressed anchorages, including the following steps: Weigh 10.0 parts of polyalkylene glycol B, 0.6 parts of sodium metasilicate, 0.3 parts of sodium polyaspartate B, and 89.1 parts of deionized water. Mix the above components evenly at room temperature to prepare a water-based quenching medium, which is then injected into the continuous quenching tank and pipeline system.
[0049] Prestressed anchors made of 40Cr material are placed in a mesh belt protective atmosphere heating furnace, which is filled with a protective gas to prevent metal oxidation and decarburization. The furnace operating temperature is set to 850℃ and the carbon potential is controlled at 0.43%C. The prestressed anchors are laid flat on a continuously moving transmission mesh belt inside the furnace. The movement of the mesh belt slowly transports the prestressed anchors from the furnace inlet to the discharge outlet. During the transport process, the prestressed anchors gradually heat up and are continuously kept at that temperature, ultimately achieving complete austenitization.
[0050] During the continuous descent of the prestressed anchors into the quenching tank, the system simultaneously executes dual-loop fluid scheduling. The main circulation pump draws fluid from the lower part of the quenching tank, passing it through the main circulation cooling heat exchanger to maintain a constant macroscopic fluid temperature of 42℃ throughout the quenching tank. Simultaneously, a liquid surface overflow pump extracts 18% of the total flow rate of side-stream fluid from the 0-150mm depth layer directly above the prestressed anchor descent area within the quenching tank. This side-stream fluid is fed into a compensating heat exchanger for heating, raising its outlet temperature to 68℃. Subsequently, the side-stream fluid enters a high-shear homogenizing pump, utilizing the narrow gap between the high-speed rotating rotor and the stationary stator inside the pump to apply pressure to the fluid for 6500 seconds. -1 Mechanical pulverization and dispersion are performed using a shear rate.
[0051] After the prestressed anchor falls into the quenching tank, it undergoes phased cooling along the conveying trajectory within the tank. Specifically, it passes through three spatial flow field zones in sequence: First, it enters the transient film-breaking zone from 0 to 3 seconds after falling into the water. In this zone, the 68°C side-stream fluid, after mechanical crushing and dispersion, is vertically sprayed upwards through the bottom jet nozzle array at a local flow velocity of 2.1 m / s, impacting the conical inner hole of the prestressed anchor. Next, it enters the film-coating and temperature-equalizing zone from 3 to 15 seconds after falling into the water. In this zone, the local flow velocity is controlled at a laminar flow state of 0.2 m / s, and the macroscopic temperature of the fluid in contact with the surface of the prestressed anchor recovers to 42°C. Finally, it enters the convective cooling zone from 15 seconds after falling into the water until exiting the tank. In this zone, the local flow velocity is controlled at 0.6 m / s, and the temperature is maintained at 42°C.
[0052] When the overall temperature of the prestressed anchor drops to 100℃, it is removed from the quenching tank. After the surface moisture is evaporated by the residual heat of the prestressed anchor, it is sent to a continuous tempering furnace and held at 200℃ for 105 minutes. After being removed from the furnace and air-cooled, the heat-treated prestressed anchor is obtained.
[0053] Example 3: This embodiment provides a continuous heat treatment process for prestressed anchorages, including the following steps: Weigh 12.0 parts of polyalkylene glycol C, 0.8 parts of sodium metasilicate, 0.4 parts of sodium polyaspartate C, and 86.8 parts of deionized water. Mix the above components evenly at room temperature to prepare a water-based quenching medium, which is then injected into the continuous quenching tank and pipeline system.
[0054] Prestressed anchors made of 40Cr material are placed in a mesh belt protective atmosphere heating furnace, which is filled with a protective gas to prevent metal oxidation and decarburization. The furnace operating temperature is set to 860℃ and the carbon potential is controlled at 0.45%C. The prestressed anchors are laid flat on a continuously moving transmission mesh belt inside the furnace. The movement of the mesh belt slowly transports the prestressed anchors from the furnace inlet to the discharge outlet. During the transport process, the prestressed anchors gradually heat up and are continuously kept at that temperature, ultimately achieving complete austenitization.
[0055] During the continuous descent of the prestressed anchors into the quenching tank, the system simultaneously executes dual-loop fluid scheduling. The main circulation pump draws fluid from the lower part of the quenching tank, passing it through the main circulation cooling heat exchanger to maintain a constant macroscopic fluid temperature of 45℃ throughout the quenching tank. Simultaneously, a liquid surface overflow pump extracts 20% of the total flow rate of side-stream fluid from a layer 0 to 200 mm above the prestressed anchor descent area within the quenching tank. This side-stream fluid is fed into a compensating heat exchanger for heating, raising its outlet temperature to 70℃. Subsequently, the side-stream fluid enters a high-shear homogenizing pump, utilizing the narrow gap between the high-speed rotating rotor and the stationary stator inside the pump to apply pressure to the fluid for 8000 seconds. -1 Mechanical pulverization and dispersion are performed using a shear rate.
[0056] After the prestressed anchor falls into the quenching tank, it undergoes phased cooling along the conveying trajectory within the tank. Specifically, it passes through three spatial flow field zones in sequence: First, it enters the transient film-breaking zone from 0 to 4 seconds after falling into the water. In this zone, the 70°C side-stream fluid, after mechanical crushing and dispersion, is vertically sprayed upwards through the bottom jet nozzle array at a local flow velocity of 2.5 m / s, impacting the conical inner hole of the prestressed anchor. Next, it enters the film-coating and temperature-equalizing zone from 4 to 18 seconds after falling into the water. In this zone, the local flow velocity is controlled at a laminar flow state of 0.3 m / s, and the macroscopic temperature of the fluid in contact with the surface of the prestressed anchor recovers to 45°C. Finally, it enters the convective cooling zone from 18 seconds after falling into the water until exiting the tank. In this zone, the local flow velocity is controlled at 0.8 m / s, and the temperature is maintained at 45°C.
[0057] When the overall temperature of the prestressed anchor drops to 120℃, it is removed from the quenching tank. After the surface moisture is evaporated by the residual heat of the prestressed anchor, it is sent to a continuous tempering furnace and held at 220℃ for 120 minutes. After being removed from the furnace and air-cooled, the heat-treated prestressed anchor is obtained.
[0058] Comparative Example 1: Compared with Example 1, the difference is that the micro-compensation heating step in the side-stream fluid microprocessor circuit is eliminated. That is, after the side-stream fluid is extracted by the liquid surface overflow pump, it does not pass through the heat exchanger for heating and directly enters the high-shear homogenizer at the original temperature of 40°C. All other aspects are the same.
[0059] Comparative Example 2: Compared with Example 1, the difference is that the high-shear homogenizing pump treatment step is omitted. The side-stream fluid heated to 65°C by the heat exchanger is directly delivered to the bottom jet nozzle array by a regular centrifugal booster pump that does not have high-shear function. All other aspects are the same.
[0060] Comparative Example 3: Compared with Example 3, the difference is that sodium metasilicate is not added to the water-based quenching medium formula, and 0.8 parts of sodium metasilicate are replaced with an equal weight of deionized water, that is, the deionized water is changed to 87.6 parts, and the rest are the same.
[0061] Comparative Example 4: Compared with Example 2, the difference is that sodium polyaspartate B is not added to the water-based quenching medium formulation, and 0.3 parts of sodium polyaspartate B are replaced with an equal weight of deionized water, that is, the deionized water is changed to 89.4 parts, and the rest are the same.
[0062] Test Example 1: After the continuous heat treatment process system for prestressed anchorages has reached a stable operating condition, sampling valves are installed at the end of the side-line microprocessor loop in Example 1, Comparative Example 1, and Comparative Example 2, i.e., at the front end of the inlet pipe of the bottom jet nozzle array, to simultaneously collect 50 mL of side-line fluid samples.
[0063] The collected side-line fluid samples were transferred to a sealed sampler with a constant temperature jacket. The jacket temperature was adjusted so that the side-line fluid samples of Example 1 and Comparative Example 2 were maintained at the calibrated temperature of 65°C, and the side-line fluid sample of Comparative Example 1 was maintained at the pipeline ambient temperature of 40°C. The samples were kept at this temperature for 3 minutes to reduce the interference of air bubbles introduced during the sampling process on the test status.
[0064] Particle size and dispersion were determined using a dynamic light scattering instrument. Each group of side-line fluid samples was injected into a quartz cuvette at the corresponding constant test temperature and placed inside the dynamic light scattering instrument test chamber.
[0065] The backscattering angle of the dynamic light scattering instrument was set to 173°. The single side-line fluid sample was continuously scanned and detected 15 times. The fluctuating light intensity signal fed back by the detector was collected. The Z-average particle size, polydispersity index coefficient and particle size distribution continuous signal of the dispersed phase in each group of side-line fluids were fitted and output by the built-in algorithm of the dynamic light scattering instrument.
[0066] Table 1: Test data on particle size and stability of the dispersed phase in the side-stream fluid Based on the data in Table 1 and Figure 1The distribution curves and physical states of the side-stream fluid correspond to the process intervention methods proposed in this application. In Example 1, the side-stream fluid, under the synergistic effect of compensated heating at 65.1℃ and a high shear field, had a measured Z-average particle size of 462.8 nm, corresponding to... Figure 1 The lateral fluid exhibits a concentrated, single-peaked distribution, and the polydispersity index of 0.143 indicates that the lateral fluid of Example 1 has a high degree of dispersion, forming a relatively uniform submicron dispersed phase, which has the physical basis for generating a continuous interfacial coating in the preceding process.
[0067] Observing the data of Comparative Example 1, the side-stream fluid of Comparative Example 1 was maintained at an ambient water temperature of 40.2℃, which is lower than the inverse melting point of the polymer component. The polymer chains tended to be in a hydrated and dissolved state, and the measured 18.6nm mainly reflects the free state of the polymer. Figure 1 The distribution curve showed no obvious enrichment peaks, and the polydispersity index was 0.712. The test data reflected that without the thermal compensation excitation step, the side-line fluid did not form a pre-precipitated state at the bottom jet nozzle array, which delayed the film formation response process of the polymer on the high-temperature metal surface.
[0068] According to Table 1, the high shear field state of Comparative Example 2 was absent, indicating that the side-stream fluid of Comparative Example 2 was not treated by a high shear homogenizing pump during pipeline transportation and lacked a mechanical crushing and dispersion step. After undergoing thermal compensation heating, the polymer in the side-stream fluid of Comparative Example 2 underwent a precipitation phase transition. Due to the lack of high shear dispersion, the precipitated polymer droplets tended to aggregate with each other, and the measured Z-average particle size increased to 5134.5 nm.
[0069] exist Figure 1 In Comparative Example 2, the distribution envelope shifts to the right towards the larger particle size range and exhibits an irregular tailing phenomenon. The polydispersity index is 0.528, indicating that the polymer dispersed phase is in an agglomerated state. The coarse and unevenly distributed polymer agglomerates cause local fluctuations in the concentration of the side-line fluid jet, making it difficult to form a uniform co-deposition layer on the complex inner surface of the prestressed anchor. Based on the above test data, the synergistic effect of the micro-compensation heating step and the high-shear treatment step on the regulation of the micro-state of the side-line fluid is verified.
[0070] Test Example 2: 100 mL of the water-based quenching medium prepared in Example 2 and Comparative Example 4 were extracted as test samples. The test samples of Example 2 and Comparative Example 4 were placed in petri dishes and placed in a vacuum drying oven. The temperature of the vacuum drying oven was set to 80°C and the absolute pressure was 0.08 MPa. The samples were dried continuously for 24 hours to remove free moisture from the test samples and obtain solid polymer dry film samples.
[0071] The chemical bonding state of the above-mentioned solid polymer dry film sample was determined using Fourier transform infrared spectroscopy. An attenuated total reflectance attachment was used during the test, and the solid polymer dry film sample was placed in close contact with the diamond crystal surface. The spectral scanning range of the Fourier transform infrared spectrometer was set to 4000 cm⁻¹. -1 Up to 400cm -1 The resolution is set to 4cm. -1 The cumulative scanning number of a single solid polymer dry film sample was set to 32 times. The test software recorded the transmittance signal of infrared light at different wavenumbers and generated an infrared spectrum, from which the wavenumber values of the absorption peak center representing the characteristic ether bond were extracted.
[0072] The thermal decomposition process of solid polymer dry film samples was tested using a simultaneous thermal analyzer. Trace amounts of debris, ranging from 10.5 mg to 11.2 mg, were cut from the solid polymer dry film samples of Example 2 and Comparative Example 4 and placed in alumina crucibles. The test environment was a high-purity nitrogen protective atmosphere, with a nitrogen purging flow rate set to 50 mL / min. The programmed temperature range was set to 30 °C to 450 °C, and the linear heating rate was controlled at 10 °C / min. The simultaneous thermal analyzer system software continuously recorded the weight loss curve of the solid polymer dry film sample as a function of temperature, and extracted the initial thermal decomposition temperature value when the mass loss rate reached 5% and the peak temperature value corresponding to the maximum thermal weight loss rate.
[0073] Table 2: Absorption Peaks and Thermal Stability Test Data of Characteristic Groups in Polymer Coating According to Table 2 and Figure 2 and Figure 3 It can be seen that there is a corresponding relationship between the differences in the composition ratio of the water-based quenching medium and the changes in the microstructure during the polymer film formation process. Figure 2 The spectral data showed that, in Comparative Example 4, no sodium polyaspartate was added; the polyalkylene glycol polymer chains exhibited an independent film-forming state. The absorption peak characterizing the stretching vibrations of the polyalkylene glycol ether bonds in the infrared spectrum was centered at 1115.7 cm⁻¹. -1 In Example 2, under formulation conditions containing sodium polyaspartate, the absorption peak center wavenumber of the ether bond shifted to a lower frequency direction to 1098.4 cm⁻¹. -1 The red shift of the absorption peak indicates that the ether bond oxygen atoms on the polyalkylene glycol molecular chain physically interact with the polar groups in the polyaspartic acid sodium molecule structure, forming an intermolecular hydrogen bond cross-linking network, which causes a change in the chemical bond force constant.
[0074] Combining the thermal analysis characteristic values in Table 2 with Figure 3It can be seen from the thermogravimetric process that the intermolecular hydrogen bond crosslinking state affects the thermal decomposition process of the polymer dry film in a high-temperature environment. For the solid polymer dry film in Comparative Example 4, an initial mass loss of 5% occurs when the temperature rises to 243.2°C, and the peak temperature corresponding to the maximum thermogravimetric rate is 312.8°C. During the temperature rise of the solid polymer dry film in Example 2, the initial thermal decomposition temperature is delayed to 278.6°C, and the temperature corresponding to the maximum thermogravimetric rate shifts to 354.2°C. The test data show that the addition of sodium polyaspartate increases the slip and desorption resistance of polymer segments under heating conditions, and increases the initial decomposition temperature of the solid polymer dry film. The above test results provide physical evidence for that the formulation system containing sodium polyaspartate improves the thermal resistance stability of the interfacial phase-change polymer coating during the high-temperature nucleate boiling stage.
[0075] Test Example 3: 20 liters each of the prepared water-based quenching media from Example 3 and Comparative Example 3 are extracted as test samples, and respectively injected into the liquid storage tank of a cooling characteristic testing device.
[0076] An Inconel 600 nickel-based alloy probe with a central blind hole structure is selected as the test object simulating the inner hole of a prestressed anchor, a K-type thermocouple is embedded on the side wall of the bottom of the central blind hole of the nickel-based alloy probe, and the thermocouple signal line is connected to the data acquisition terminal of the cooling characteristic testing device.
[0077] The nickel-based alloy probe equipped with the thermocouple is placed in a tube furnace, the heating temperature of the tube furnace is set to 850°C, and the heating state is maintained for 30 minutes to make the overall temperature distribution of the nickel-based alloy probe uniform.
[0078] Start the jet pump of the cooling characteristic testing device, adjust the flow rate of the water-based quenching medium to the set constant value, transfer the heated nickel-based alloy probe into the test chamber, control the bottom nozzle to align with the central blind hole of the nickel-based alloy probe, and continuously spray the water-based quenching medium to perform a cooling experiment.
[0079] The data acquisition terminal continuously records the temperature change signal with time during the temperature reduction process of the nickel-based alloy probe, performs differential operation processing on the temperature change signal with time by using the analysis software matched with the data acquisition terminal, outputs a temperature-time curve and a cooling rate-temperature curve, and extracts the characteristic temperature value and the maximum cooling rate value from the curves; the characteristic temperature is defined as the critical temperature when the heat transfer process changes from film boiling to nucleate boiling.
[0080] Table 3: Test data table of cooling characteristics under inner hole simulated flow field According to Table 3 and Figure 4It can be seen that the addition state of sodium metasilicate in the water-based quenching medium is directly related to the heat exchange evolution process inside the blind hole of the nickel-based alloy probe. Figure 4 The trajectory distribution of the hollow cube in Comparative Example 3. The water-based quenching medium formulation of Comparative Example 3 did not contain sodium metasilicate. In the initial and medium-high temperature cooling range from 850°C to about 485°C, the hollow cube slowly decreased over time, and the cube size remained in a very small state. The above morphological characteristics reflect that a continuous and stable film boiling layer is formed at the gas-liquid interface inside the blind hole of the nickel-based alloy probe. The presence of the gas film layer hinders the heat exchange efficiency between the water-based quenching medium and the metal surface of Comparative Example 3. The size of the hollow cube only expands when the temperature drops above the characteristic temperature limit of 485.2°C, indicating that the film boiling slowly breaks down and enters the nucleation boiling stage.
[0081] Example 3's water-based quenching medium formulation contains sodium metasilicate, which is derived from... Figure 4 As can be seen from the evolution trajectory of solid dot Example 3, when the solid dot of Example 3 drops to around 724.6℃, the graphic size of the solid dot increases explosively. This visual feature corresponds to the characteristic temperature of Example 3 in Table 3 being raised to 724.6℃.
[0082] The above test phenomena confirm the physical intervention mechanism of sodium metasilicate in the high-temperature metal interface region: sodium metasilicate undergoes a local dehydration and crystallization reaction on the high-temperature metal surface, and the generated solid particles adhere to the solid-liquid interface. The attached solid particles cause physical protrusions and disturbances to the originally smooth gas film layer, disrupting the hydrodynamic equilibrium of the film boiling layer at high temperature. The intervention of solid particles causes the heat transfer mode inside the blind hole of the nickel-based alloy probe to change to nucleation boiling with extremely high heat transfer efficiency in a higher temperature range.
[0083] Combination Figure 4 The peak state of the scattered point size and the maximum cooling rate values in Table 3 show that the maximum cooling rate of Comparative Example 3 is 112.4℃ / s, and the peak size appears in the low-temperature range of 415.8℃. The maximum cooling rate of Example 3 reaches 178.5℃ / s, and the position where the solid circle size reaches the maximum peak value moves forward to the high temperature direction to 592.3℃. The various physical state data corroborate each other, indicating that the formulation system containing sodium metasilicate exhibits the characteristic of breaking the closed state of the high-temperature gas film inside the deep pore. The above experimental results provide test support for the innovative mechanism of sodium metasilicate component participating in the regulation of the boiling heat transfer process of the variable cross-section internal pore structure.
[0084] Test Example 4: 40Cr alloy structural steel prestressed anchor blanks with chemical composition conforming to national standards were selected as test samples. 100 liters of water-based quenching media prepared in Example 1 and Comparative Example 1 were extracted and injected into the circulating liquid tank of the quenching test bench, respectively.
[0085] The prestressed anchor blank is sent into a continuous multi-purpose heating furnace for austenitization treatment. The temperature of the high-temperature zone of the continuous multi-purpose heating furnace is set to 850℃, and the holding time of the prestressed anchor blank in the high-temperature zone of the continuous multi-purpose heating furnace is set to 45 minutes, so that the internal structure of the prestressed anchor blank undergoes austenitic transformation.
[0086] The prestressed anchor blanks that have undergone austenitization treatment were immersed in quenching test benches containing water-based quenching media of Example 1 and Comparative Example 1, respectively. The bottom inner hole jet system of the quenching test bench was started simultaneously, and the inner hole jet pressure was maintained at 0.15 MPa. The cooling was continued for 5 minutes until the overall temperature of the prestressed anchor blanks dropped to room temperature.
[0087] The cooled prestressed anchor blank was longitudinally cut along the central axis using an electrical discharge wire cutting device to obtain a longitudinal section block of the prestressed anchor. The test surface of the longitudinal section block of the prestressed anchor was sanded and mechanically polished step by step, and the test surface of the polished prestressed anchor longitudinal section block was subjected to metallographic corrosion using a 4% nitric acid alcohol solution.
[0088] A micro Vickers hardness tester was used to perform matrix-style multi-point hardness measurements in the area below the inner hole wall of the longitudinal section block of the prestressed anchor. The hardness test load was set to 500 gf and the holding time was set to 15 seconds. The hardness values at each spatial coordinate test point were recorded, and the standard deviation range of the hardness of the entire test surface of the longitudinal section block of the prestressed anchor was calculated. A metallographic microscope combined with image analysis software was used to determine the martensite phase volume percentage at a depth of 1.0 mm vertically downward from the inner hole wall surface. A coordinate measuring machine was used to scan the cylindricity of the inner hole of the prestressed anchor before and after quenching, and the cylindricity deformation increment of the inner hole of the prestressed anchor was recorded.
[0089] Table 4: Vickers Hardness and Martensitic Transformation Test Data for Inner Hole Section According to Table 4 and Figure 5 It can be seen that the difference in cooling characteristics of the water-based quenching medium in the flow field within the prestressed anchorage's inner hole is transformed into the final mechanical properties and form and position tolerances. Figure 5 (b) shows the contour lines. In the middle section of the inner hole of the prestressed anchor test sample of Comparative Example 1, the hardness contour lines show a downward concave shape, and the lowest hardness value in the center drops to below 450HV. According to the records in Table 4, the average Vickers hardness of the inner hole surface of Comparative Example 1 is 467.4, and the range of the matrix hardness standard deviation is 45.6 to 62.8.
[0090] The above data reflects the physical phenomenon of delayed vapor film accumulation in the deep hole structure of conventional water-based fluids. The continuous presence of the vapor film blocks the heat exchange between the metal in the middle section of the prestressed anchor hole and the water-based quenching medium. The reduction in cooling rate restricts the driving force for the transformation of supercooled austenite to martensite. In Table 4, the volume percentage of martensite at a depth of 1.0 mm in Comparative Example 1 is 72.4%, indicating that a non-martensitic transformation of the microstructure occurs locally in the inner hole of the prestressed anchor. The asynchronous process of microstructure transformation and the uneven distribution of local thermal stress lead to an increase in the cylindricity deformation of the inner hole of the prestressed anchor test sample of Comparative Example 1 reaching 0.086 mm.
[0091] Compared with the test results of Example 1, by Figure 5 (a) It can be seen that the hardness contour lines of Example 1 extend approximately parallel to the axial direction of the inner hole of the prestressed anchor, and no local hardness collapse area appears. The data in Table 4 show that the average Vickers hardness of the inner hole surface of Example 1 is increased to 543.8, and the matrix hardness standard deviation range value is maintained in the range of 10.5 to 13.2. The uniformity of hardness distribution corresponds to the synchronicity of the martensitic phase transformation process. The martensite volume percentage at a depth of 1.0 mm in Example 1 is increased to 91.7%.
[0092] The water-based quenching medium formulation system corresponding to Example 1 changes the existence state of the boiling phase change gas film in the internal flow field, reduces the local cooling blind zone inside the deep hole, and makes the surface cooling rate of the inner hole wall of the prestressed anchor test sample tend to be consistent, reducing the internal stress caused by the time difference of the specific volume change. The reduction of physical stress controls the cylindricity deformation increment of the inner hole in Example 1 to 0.021 mm. The above mechanical and metallographic indicators verify that the water-based quenching medium formulation provided in this application has the test performance of improving the heat treatment hardness uniformity of complex tube-shaped structural parts.
[0093] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A continuous heat treatment process for prestressed anchorages, characterized in that, include: Prepare water-based quenching medium and inject it into the quenching tank and pipeline; The prestressed anchorage is placed in a heating furnace for heat preservation to achieve complete austenitization; During the process of the prestressed anchor falling into the quenching tank, a dual-loop fluid scheduling is performed: the main circulation pump draws the fluid from the lower part of the quenching tank, and the water temperature in the quenching tank is kept constant through the main circulation cooling heat exchanger; the liquid level overflow pump extracts the upper part of the fluid below the liquid level in the quenching tank as the side-line fluid, and the side-line fluid is heated by the heat exchanger and then fed into the high-shear homogenizing pump to apply shear force through the stator-rotor gap for mechanical crushing and dispersion. After being mechanically crushed and dispersed, the side-stream fluid is sprayed vertically upward through the bottom jet nozzle array to impact the conical inner hole of the prestressed anchor falling into the quenching tank for staged cooling. After the prestressed anchorage cools down, it is removed from the quenching tank and sent to the tempering furnace for heat preservation. After being taken out of the furnace and air-cooled, the heat-treated prestressed anchorage is obtained.
2. The continuous heat treatment process for prestressed anchorages according to claim 1, characterized in that, The water-based quenching medium is made from the following raw materials in parts by weight: Deionized water: 86.8 to 91.4 parts; Polyalkylene glycol: 8.0 to 12.0 parts; Sodium metasilicate: 0.4 to 0.8 parts; Sodium polyaspartate: 0.2 to 0.4 parts.
3. The continuous heat treatment process for prestressed anchorages according to claim 2, characterized in that, The polyalkylene glycol is made from the following raw materials in parts by weight: n-Butanol: 0.55 to 0.60 parts; Potassium hydroxide: 0.1 to 0.3 parts; Ethylene oxide: 45.0 to 55.0 parts; Propylene oxide: 45.0 to 66.0 parts.
4. The continuous heat treatment process for prestressed anchorages according to claim 2, characterized in that, The sodium polyaspartate is made from the following raw materials in parts by weight: L-Aspartic acid: 100.0 to 110.0 parts; Deionized water: 180.0 to 220.0 parts; A 20% to 30% sodium hydroxide aqueous solution: 110.0 to 150.0 parts by mass.
5. The continuous heat treatment process for prestressed anchorages according to claim 1, characterized in that, In the step of placing the prestressed anchor in a heating furnace for heat preservation to achieve complete austenitization, the operating temperature of the heating furnace is 840°C to 860°C, and the carbon potential is 0.40%C to 0.45%C. In the step of removing the prestressed anchor from the quenching tank after it has cooled down and sending it to the tempering furnace for heat preservation, the temperature of the prestressed anchor is 80℃ to 120℃ when it is removed from the quenching tank; the working temperature of the tempering furnace is 180℃ to 220℃, and the heat preservation time is 90 to 120 minutes.
6. The continuous heat treatment process for prestressed anchorages according to claim 1, characterized in that, In the step of the main circulation pump drawing fluid from the lower part of the quenching tank and maintaining the water temperature in the quenching tank at a constant temperature of 40°C to 45°C via the main circulation cooling heat exchanger; The overflow pump extracts the upper fluid below the liquid surface in the quenching tank as a side-stream fluid. After being heated by a heat exchanger, the side-stream fluid is fed into a high-shear homogenizing pump for mechanical pulverization and dispersion using shear force applied by the stator-rotor gap. The side-stream fluid is extracted from a depth of 0 to 200 mm below the liquid surface directly above the prestressed anchor's water-falling area, accounting for 15% to 20% of the total flow rate. The heated side-stream fluid reaches a temperature of 65°C to 70°C. The high-shear homogenizing pump applies a shear rate of 5000 s⁻¹. -1 up to 8000s -1 .
7. The continuous heat treatment process for prestressed anchorages according to claim 1, characterized in that, The specific steps for staged cooling and temperature reduction are as follows: the prestressed anchor sequentially undergoes a transient film-breaking zone, a coating homogenization zone, and a convection cooling zone within the quenching tank. The transient film-breaking zone lasts for 2 to 4 seconds, with the side-stream fluid being vertically injected upwards at a local flow velocity of 1.8 m / s to 2.5 m / s. The coating homogenization zone lasts for 10 to 14 seconds, with a local flow velocity of 0.1 m / s to 0.3 m / s in a laminar flow state. The convection cooling zone continues until the prestressed anchor is removed from the quenching tank, with a local flow velocity of 0.5 m / s to 0.8 m / s.
8. The continuous heat treatment process for prestressed anchorages according to claim 2, characterized in that, The polyalkylene glycol has a weight-average molecular weight of 12,050 to 14,960 and a cloud point of 60°C to 65°C for a 10% aqueous solution; the sodium polyaspartate has a weight-average molecular weight of 3,120 to 4,950.
9. The continuous heat treatment process for prestressed anchorages according to claim 1, characterized in that, The bottom jet nozzle array is located at the bottom of the quenching tank, and is used to make the side jet fluid spray vertically upward and impact the conical inner hole of the prestressed anchor falling into the quenching tank.
10. A system for a continuous heat treatment process for prestressed anchorages according to any one of claims 1-9, characterized in that, include: A heating furnace is used to place and heat-insulate prestressed anchorages to achieve complete austenitization. Quenching tank, used to contain water-based quenching medium and receive prestressed anchors dropped into it; The main circulation pump and the main circulation cooling heat exchanger are connected to the lower part of the quenching tank to extract fluid from the lower part of the quenching tank. The main circulation cooling heat exchanger is connected to the main circulation pump and is used to cool the extracted fluid and circulate it back to the quenching tank to maintain a constant water temperature in the quenching tank. The system consists of a liquid level overflow pump, a heat exchanger, and a high-shear homogenizing pump connected in series. The liquid level overflow pump is used to extract the upper fluid below the liquid level in the quenching tank as a side-stream fluid. The heat exchanger is used to heat the side-stream fluid. The high-shear homogenizing pump is used to apply shear force to the heated side-stream fluid using the stator-rotor gap for mechanical crushing and dispersion. The bottom jet nozzle array is connected to the outlet of the high-shear homogenizing pump and located at the bottom of the quenching tank. It is used to vertically spray the side-stream fluid after mechanical crushing and dispersion upwards to impact the conical inner hole of the prestressed anchor that falls into the quenching tank. A tempering furnace is used to receive prestressed anchors that have been removed from the quenching tank.